“I couldn’t stand it and exploted”: The expression of femenine “nervousness” in the care of children in the favela territories - Fernandes, Camila (Instituto de Altos Estudios Sociales, 2020)
Motherhood as a collective representation is situated in a field full of ambivalence. If, on the one hand, we have an imaginary abundance of devotion, sacrifice and maternal loving, on the other, we have feelings of hatred, nervousness and tiredness equally present. However, while “positive” feelings are adequately socially conveyed, “negative” expressions of motherhood are sometimes censored, stifled or worthy of public scrutiny. Based on field work carried out with women living in favelas, I examine the anger and nervousness that poor women experience in relation to their children. In the course of research conducted with residents and state institutions, “nervous” women were part of a system of accusations about social disorders. Such women are criticized for beating, humiliating and punishing their children. Listening to the stories of these women about their care relationships, I analyze the place of anger and nervousness in a terrain marked by compulsory attention.